Progression-related loss of stromal caveolin 1 levels mediates radiation resistance in prostate carcinoma via the apoptosis inhibitor TRIAP1 - Ketteler, Julia; Maier, Patrick; Herskind, Carsten (Journal of Clinical Medicine, 2019)
Tumour resistance to chemo- and radiotherapy, as well as molecularly targeted therapies, limits the effectiveness of current cancer treatments. We previously reported that the radiation response of human prostate tumours is critically regulated by CAV1 expression in stromal fibroblasts and that loss of stromal CAV1 expression in advanced tumour stages may contribute to tumour radiotherapy resistance. Here we investigated whether fibroblast secreted anti-apoptotic proteins could induce radiation resistance of prostate cancer cells in a CAV1-dependent manner and identified TRIAP1 (TP53 Regulated Inhibitor of Apoptosis 1) as a resistance-promoting CAV1-dependent factor. TRIAP1 expression and secretion was significantly higher in CAV1-deficient fibroblasts and secreted TRIAP1 was able to induce radiation resistance of PC3 and LNCaP prostate cancer cells in vitro, as well as of PC3 prostate xenografts derived from co-implantation of PC3 cells with TRIAP1-expressing fibroblasts in vivo. Immunohistochemical analyses of irradiated PC3 xenograft tumours, as well as of human prostate tissue specimen, confirmed that the characteristic alterations in stromal-epithelial CAV1 expression were accompanied by increased TRIAP1 levels after radiation in xenograft tumours and within advanced prostate cancer tissues, potentially mediating resistance to radiation treatment. In conclusion, we have determined the role of CAV1 alterations potentially induced by the CAV1-deficient, and more reactive, stroma in radio sensitivity of prostate carcinoma at a molecular level. We suggest that blocking TRIAP1 activity and thus avoiding drug resistance may offer a promising drug development strategy for inhibiting resistance-promoting CAV1-dependent signals.